Peran Self regulation dan Social support terhadap Adiksi Media Sosial pada Pelajar SMK - Muhamad Luki Efendi; Amanda Pasca Rini; Eko April Ariyanto (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract This study examines the relationship between self-regulation and social support with social media addiction among vocational high school students. Indonesia ranks high in both the number of social media users and the average duration of daily usage, which potentially increases the risk of addiction, particularly among adolescents. A correlational quantitative approach was used to determine the extent to which these two variables are associated with tendencies toward social media addiction. The findings of this study are expected to serve as a foundation for developing intervention strategies aimed at preventing and addressing social media addiction in educational settings.. Keywords: self regulation, social support, social media addiction, vocational school students Abstrak Penelitian ini mengkaji hubungan antara self regulation dan social support dengan adiksi media sosial pada pelajar Sekolah Menengah Kejuruan (SMK). Indonesia menempati peringkat tinggi dalam jumlah pengguna dan durasi penggunaan media sosial, yang berpotensi meningkatkan risiko adiksi, khususnya di kalangan remaja. Penelitian ini menggunakan pendekatan kuantitatif korelasional untuk melihat sejauh mana kedua variabel tersebut berkaitan dengan kecenderungan adiksi media sosial. Hasil penelitian ini diharapkan dapat menjadi dasar dalam pengembangan strategi intervensi untuk pencegahan dan penanganan adiksi media sosial di lingkungan pendidikan. Kata kunci: self regulation, social support, adiksi media sosial, pelajar SMK.